Jadis, dans le commencement la parole n’était pas: A Study of the Linguistic Strategies of Digital Travel Promotions in French - Álvares, Cristina (Çédille, 2019)
What is the sacred? From Georges Bataille to René Girard, throughout Roger Caillois, Mary Douglas, Julia Kristeva, Emmanuel Lévinas, the main theories of the sacred have discribed it as a notion which can hardly be contained within the framework of a definition, as its ways are exces, overflow, outburst. Frequently thought as substance and strengh, the sacred is what destabilizes forms and removes differences and borders. This line of thought is at work in Pascal Quignard’s speculations on the role of the sacred in the shaping of the human from, in and with the animal. This paper examines the sacred in the shiftings of the treshold where (proto)human animals and other animals meet